Model of Training Learning Based on Video Tutorial for Fashion Major of Vocational Education on Embroidery Course - Yuliarma,; Yan Yan Sunarya,; Kudiya, Komarudin; Rasul, Muhammad Sattar; Fuja Novitra, (Journal of Technical Education and Training, 2024)
Students' difficulties in understanding innovative design concepts in fashion major of vocational education require a learning model that has a balance between theory and practice to facilitate understanding and improve students' practical skills.  This study aims to develop a valid, practical, and effective training learning model based on video tutorials on Minangkabau embroidery learning material. The research is a Design and Development Research (DDR) using the ADDIE framework. The research subjects involved experts namely media experts, learning material experts, design experts, and learning experts to assess the validity of the learning model, and the experimental subjects involved Fashion Major of vocational education on undergraduate students. Data collection in the study was carried out using questionnaires, learning achievement tests, and observation sheets. The results indicate a significant contribution to enhancing the cognitive, affective, skill, and attitude abilities of Fashion Education undergraduate students. These results also indicate that this model meets the criteria of valid, practical, and effective. The implications of these findings underscore the potential positive impact of the developed tutorial model on the overall learning experience and outcomes in Fashion Education.